Comunicação e apropriação do espaço em ambientes sociais online
In contemporary culture of simulation, this communication aims at contributing to the debate on the construction, overhaul and new switching identities in online social environments, "selves" ubiquitous, plural, reflexive and hyper-modern. In an attempt to come to some conclusions, it is proposed to discuss new paradigms of communication and appropriation of space in these environments (and in particular in Second Life), looking to see how a culture of simulation is manifested in these contexts. A discussion of these issues will lead to some fundamental questions understood as: - The new paradigms of perception and appropriation of space, or a virtual contemplation mobilized, will detect, in social environments online, new models of communication and interpersonal relations? - Are these paradigms result of hedonistic attitudes and hyper-modern (post-ideological as) before or constitute the pillars of collaborative environments for knowledge building and citizenship? - Confirmed the existence carried over these models, experienced online to RL (real life) contemporary, where (individuals) simulators are constituted as "new settlers"? This communication tries to bring to the discussion the possible emergence of a process of "colonization" online based on ownership of a space of flows and non-places and the construction of new communication codes, recognizing the existence of a feedback process that will make in real life, the "new settlers" change their ways of communicating and format your interpersonal relationships and space. Sustaining this reflection, it seems appropriate to analyze the notions of presence, illusion of life and understanding of space as a means. Empirical data derived from experience teaching in Second Life will attempt to illustrate some of the ideas outlined above, and are part of a qualitative online research process currently underway.